PENERAPAN REHABILITASI TERHADAP PENYALAHGUNA NARKOTIKA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA DI KABUPATEN SIAK - Muhammad Ragel; Erdianto Effendi; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
According to Article 54 of Law Number 35 Year 2009 concerning Narcotics, narcotics addicts and narcotics abusers must undergo rehabilitation. But in the application in Siak Regency, rehabilitation is only an expectation of narcotics addicts and users to get treatment and treatment. The purpose of writing this thesis are: First, the application of rehabilitation of narcotics abusers in Siak Regency, Second, the obstacles experienced by law enforcement officials in the application of rehabilitation of narcotics abusers in Siak Regency.This type of research can be classified in the type of empirical juridical research or sociological research, because in this study the authors directly carry out research at the location under study in order to provide a complete and clear picture of the problem under study. This research was conducted in Siak District, namely in the Siak District Court, Siak Resort Police, and Pekanbaru Class IIA Penitentiary, while the population and sample were all related to the problem under study, the data source used primary data, secondary data and tertiary data , data collection techniques in this study with interview observations and literature studies.From the results of the research problem there are two main things that can be concluded. First, the implementation of rehabilitation of narcotics abusers in Siak Regency has never been implemented by law enforcement officials and the government. Second, the obstacles faced by law enforcers in implementing rehabilitation of narcotics abusers in Siak Regency namely, the absence of the District Narcotics Agency and the Integrated Assessment Team, lack of knowledge of law enforcement officials, lack of rehabilitation institutions, budgets. The author's suggestion is that the Government needs to provide assistance for the implementation of this rehabilitation in Siak Regency, then the quality and quantity of law enforcement officials need to be developed, and the need for special attention from the Government and law enforcement officials.Keywords: Implementation, Rehabilitation, Narcotics Abuser